An Unusual Complication of Transarterial Radioembolization: Hepatic Artery Pseudoaneurysm and its Treatment with Ultrasound-guided Thrombin Injection - Muhammet Arslan; Halil Serdar Aslan; Burak Sarılar; Aziz Gültekin (The Arab Journal of Interventional Radiology)
Transarterial radioembolization (TARE) is a widely used treatment method for primary liver cancers and metastasis. Although TARE is relatively safe, it may cause liver abscess, failure, nontarget embolization, and vascular complications. Herein, we report a case of TARE-related hepatic artery pseudoaneurysm that was treated successfully with ultrasound-guided thrombin injection.